DYNAMICS OF SHARIA BANKING IN IMPROVING COMMUNITY EMPOWERMENT OF MICRO SMALL AND MEDIUM ENTERPRISES (UMKM) IN PASURUAN DISTRICT (Case Study at KCP Pandaan Sharia Bank) - Erwan Aristyanto; Muhamad Fathkur Rochim (WORLDVIEW ( Development economic and sharia studies journal ), 2023)
This study discusses Islamic banking in increasing community empowerment of Micro, Small and Medium Enterprises (MSMEs) in Pasuruan Regency, to find out the role of Islamic banking in increasing MSMEs in Pasuruan Regency and to find out MSMEs actors in utilizing Islamic banking to increase their business. The authors used a qualitative descriptive research type, namely field research conducted at the Indonesian Sharia Bank KCP Pandaan. There are two sources of data used in this study, namely primary data sources and secondary data sources. Primary data sources are data obtained directly from customers Bank Syariah Indonesia KCP Pandaan. This data source comes from data obtained through interviews with informants and secondary data in research in the form of documentation. Based on the results of the research conducted, it can be concluded that the existence of Bank Syariah Indonesia KCP Pandaan provides results and impacts on MSMEs actors in Pasuruan Regency. This can be concluded because MSME actors are getting better and developing after financing at KCP Pandaan Sharia Bank. So the efforts made by Bank Syariah Indonesia KCP Pandaan in increasing MSMEs are increasing products and marketing strategies through the Community Empowerment program.